Effects of age on contractile and enzyme-histochemical properties of fast- and slow-twitch single motor units in the rat. - Edström, L (1987)
1. Contractile, enzyme-histochemical and morphometrical properties of muscle fibres were studied in single motor units of tibialis anterior (t.a.) and soleus muscles in young (3-6 months) and old (20-24 months) male albino rats. The technique of measuring glycogen depletion as a marker of previous muscle contraction was used for direct correlation of enzyme-histochemical and contractile parameters within single motor units of the fast- and slow-twitch type. 2. In t.a., the fast-twitch motor units covered 18 +/- 9 and 22 +/- 16% (P = not significant, n.s.) of t.a. cross-sections, included 148 +/- 65 and 162 +/- 63 muscle fibres per unit (P = n.s.) and had a cross-sectional area of 0.50 +/- 0.32 and 0.44 +/- 0.22 mm2 (P = n.s.) in the young and old animals, respectively (means +/- S.D.). 3. In soleus, the slow-twitch motor units covered 53 +/- 11 and 71 +/- 12% (P = n.s.), included 55 +/- 10 and 83 +/- 13 muscle fibres per unit (P less than 0.01) and had a total cross-sectional area of 0.14 +/- 0.02 and 0.22 +/- 0.06 mm2 (P less than 0.01) in the young and the old animals, respectively. The calculated number of motor units in soleus accordingly decreased (P less than 0.01) from 49 +/- 10 in the young to 29 +/- 10 in the old animals resulting in a loss of muscle fibres and an increased innervation ratio in old age (mean +/- S.D.). 4. Clusters of more than three muscle fibres were rarely seen in any of the glycogen-depleted motor units in either the young or the old animals. However, in the slow-twitch motor units of old animals the muscle fibres were less randomly distributed within the motor unit territory (P less than 0.05), indicating a denervation-reinnervation process. 5. The contraction and half-relaxation times of the isometric twitch were significantly prolonged in old age. In 274 randomly isolated single motor units of t.a. the contraction time increased from 13 +/- 1 in young animals to 17 +/- 3 ms in old ones and the half-relaxation time from 12 +/- 2 to 16 +/- 5 ms (P less than 0.01 in both cases). In 236 randomly isolated soleus single motor units, the contraction and half-relaxation times increased (P less than 0.001) from 24 +/- 5 to 31 +/- 7 ms and from 26 +/- 8 to 35 +/- 9 ms, respectively (mean +/- S.D.).(ABSTRACT TRUNCATED AT 400 WORDS)